2016
DOI: 10.4049/jimmunol.1600782
|View full text |Cite
|
Sign up to set email alerts
|

CD40-Mediated NF-κB Activation in B Cells Is Increased in Multiple Sclerosis and Modulated by Therapeutics

Abstract: CD40 interacts with CD40 ligand and plays an essential role in immune regulation and homeostasis. Recent research findings, however, support a pathogenic role of CD40 in a number of autoimmune diseases. We previously showed that memory B cells from relapsing-remitting multiple sclerosis (RRMS) patients exhibited enhanced proliferation with CD40 stimulation compared to healthy donors. In this study, we used a multi-parameter phosflow approach to analyze the phosphorylation status of NFκB and three major MAP kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 42 publications
2
33
0
1
Order By: Relevance
“…It was previously shown that okadaic acid, an inhibitor of PP1 and PP2A, provoked NF-B phosphorylation in MG63 human osteosarcoma cells, but the specific contribution of PP1␣ was not explored (30). In our study, costimulation-related NF-B activity was determined by measuring the phosphorylation (Ser529) of the p65 subunit and its translocation to the nucleus by imaging flow cytometry (31)(32)(33). While costimulation induced the phosphorylation of NF-B (p65) in control siRNA-treated cells, this phosphorylation was completely inhibited in the PP1 KD cells ( Fig.…”
Section: Figmentioning
confidence: 86%
“…It was previously shown that okadaic acid, an inhibitor of PP1 and PP2A, provoked NF-B phosphorylation in MG63 human osteosarcoma cells, but the specific contribution of PP1␣ was not explored (30). In our study, costimulation-related NF-B activity was determined by measuring the phosphorylation (Ser529) of the p65 subunit and its translocation to the nucleus by imaging flow cytometry (31)(32)(33). While costimulation induced the phosphorylation of NF-B (p65) in control siRNA-treated cells, this phosphorylation was completely inhibited in the PP1 KD cells ( Fig.…”
Section: Figmentioning
confidence: 86%
“…In line with the differences found here, aberrant STAT phosphorylation signaling in peripheral blood mononuclear cells from MS patients has been reported (28) . The NFkβ pathway has been reported to be overactivated in PBMCs from patients with MS (29,30) as well as to contribute to the genetic susceptibility of the disease (31,32) . Our analysis supports the systemic pro-inflammatory state of PBMCs in MS.…”
Section: Discussionmentioning
confidence: 99%
“…It has a wide range of symptoms including mental, physical, and psychological problems according to the recent Atlas of MS (2013) published by the MS International Federation. The global median prevalence of MS has increased from 30 to 33 cases per 100,000 people from 2008 to 2013 respectively [2,4]. Significantly, the prevalence rate of MS in Jordan increased to 39 per 100,000 people in the period from 2004 to 2005 [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most non-human leukocyte antigen (non-HLA) loci is found within the cluster of differentiation 40 (CD40) gene [11]. Recent studies support the pathogenic role of CD40 in a number of autoimmune diseases including MS [4]. CD40 belongs to the tumor necrosis factor (TNF) receptor superfamily and is expressed mainly on B cells, microglia, macrophages, and other antigen-presenting cells (APCs) [9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation